MORPHOLOGICAL PRECURSORS (FIRST INDICATIONS) OF VOLCANIC ERUPTIONS IN KAMCHATKA - Dvigalo V.N. (My University, 2001)
The air photographs of the craters of Kamchatkan volcanoes, collected during the last three decades, were decoded, photogrammetrically processed, and interpreted to recognize the features and phenomena which can be used as precursors of volcanic eruptions. These features were recognized primarily for the volcanoes which were provided with the materials of the longest aerial photography series. These are the most active volcanoes of the Klyuchevskoi group: Shiveluch, Klyuchevskoi, Bezymyannyi, and Malyi Semyachik located in the Karymskii caldera. It is shown that regular airphototopographic observations yield high-precision information of all changes that occur in the morphology of active volcanoes.